2020
DOI: 10.1101/2020.02.17.953026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral features of motivated response to alcohol inDrosophila

Abstract: Animals avoid predators and find the best food and mates by learning from the consequences of their behavior. However, reinforcers are not always uniquely appetitive or aversive but can have complex properties. Most intoxicating substances fall within this category; provoking aversive sensory and physiological reactions while simultaneously inducing overwhelming appetitive properties. Here we describe the subtle behavioral features associated with continued seeking for alcohol despite aversive consequences. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Similar responses to social stress and reward-seeking behaviors can be seen in a variety of animals, suggesting that the central systems facilitating survival and reproduction originated early in evolution and that similar ancient basic building blocks mediate these processes [ 41 , 42 ]. In agreement with this concept, we and others showed that Drosophila melanogaster can adjust its behavior and physiology to various social conditions [ 43 55 ] and that the brains of mammals and fruit flies share similar principles in encoding stress and reward [ 43 , 56 58 ]. For example, the fly homologue of the NPY signaling system (i.e., NPY and its receptor) functions in processing natural and drug rewards, decreases aggressive behaviors and suppresses responses to aversive stimuli such as harsh physical environments [ 43 , 59 69 ].…”
Section: Introductionsupporting
confidence: 71%
“…Similar responses to social stress and reward-seeking behaviors can be seen in a variety of animals, suggesting that the central systems facilitating survival and reproduction originated early in evolution and that similar ancient basic building blocks mediate these processes [ 41 , 42 ]. In agreement with this concept, we and others showed that Drosophila melanogaster can adjust its behavior and physiology to various social conditions [ 43 55 ] and that the brains of mammals and fruit flies share similar principles in encoding stress and reward [ 43 , 56 58 ]. For example, the fly homologue of the NPY signaling system (i.e., NPY and its receptor) functions in processing natural and drug rewards, decreases aggressive behaviors and suppresses responses to aversive stimuli such as harsh physical environments [ 43 , 59 69 ].…”
Section: Introductionsupporting
confidence: 71%
“…In agreement with this concept, we and others showed that Drosophila melanogaster display the ability to adjust their behavior and physiology to various changes in their social environment [40][41][42][43][44][45][46][47][48][49][50][51][52] . Moreover, recent studies provided evidence that the brains of mammals and fruit flies share similar principles when it comes to encoding stress and reward 40,[53][54][55] . The homologs for NPY and CRF in Drosophila are Neuropeptide F (NPF) and Diuretic hormone 44 (Dh44), respectively [56][57][58] .…”
Section: Introductionmentioning
confidence: 99%